2017
DOI: 10.15171/apb.2017.024
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Parameters and Over-Responsiveness of Iranian Population to Propranolol

Abstract: Purpose: Propranolol is the most widely used treatment for cardiovascular diseases. Dosage range in our patients is usually less than the amount mentioned in references. The aim of the present study was to clarify whether pharmacokinetic differences are able to justify the need for the fewer doses in our patients or not.Methods: Twenty healthy volunteers (10 male) at heart center of Mazandaran University of Medical Sciences were studied. Samples of blood were collected before a single oral dose (40 mg) of Prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…There are different studies in the literature about the effect of propranolol on genes. (32) The mechanisms underlying the properties of propranolol in gene expression are unclear at present. To explain these mechanisms more comprehensive investigations (in vivo and in vitro) should be carried out with different doses of propranolol and the protein levels in 3D cultures should be determined in future.…”
Section: Discussionmentioning
confidence: 99%
“…There are different studies in the literature about the effect of propranolol on genes. (32) The mechanisms underlying the properties of propranolol in gene expression are unclear at present. To explain these mechanisms more comprehensive investigations (in vivo and in vitro) should be carried out with different doses of propranolol and the protein levels in 3D cultures should be determined in future.…”
Section: Discussionmentioning
confidence: 99%
“…A study done by Leineweber et al, 2007, in sample of German population showed that less post-surgical inotropic support is required in patients undergoing CABG who were preoperatively chronically treated with metoprolol and homozygous for the Arg389-β 1 AR, than those with one or two Gly389-β 1 AR alleles [14]. Over-responsiveness to propranolol has been reported in Iranian population that may be associated with polymorphism of β-adrenoceptors [15]. Furthermore, it was observed that Arg16Gly-β 2 AR genotype may have protective effect for hypertension in comparison with Arg16Arg-β 2 AR variant in Iranian population [16].…”
Section: Introductionmentioning
confidence: 99%